Iodine catalysis: A green alternative to transition metals in organic chemistry and technology; Resource-Efficient Technologies; Vol. 1, iss. 1 - Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich) (2015, 2015)
Title screen